Peritoneal Protein Clearance Is Associated With Cardiovascular Events but Not Mortality in Peritoneal Dialysis Patients - Niu, Wei; Yang, Xiaoxiao; Yan, Hao; Yu, Zanzhe; Li, Zhenyuan; Lin, Xinghui; Gu, Leyi; Ni, Zhaohui; Fang, Wei (Frontiers in Medicine, 2022)
Introduction Association of peritoneal protein clearance (Pcl) with outcomes in patients with peritoneal dialysis (PD) is uncertain. Thus, we aimed to investigate its impact on cardiovascular events and all-cause mortality in patients with PD and factors associated with Pcl. Methods Prevalent patients with PD from January 2014 to April 2015 in the center of Renji Hospital were enrolled. At the time of enrollment, serum and dialysate samples were collected to detect biochemical parameters and Angiopoietin-2-Tie2 system cytokines. Mass transfer area coefficient of creatinine (MTACcr) and Pcl were calculated. Patients were dichotomized into two groups by the median Pcl level (68.5 ml/day) and were followed up prospectively until the end of the study (1 October 2018). Results A total of 318 patients with PD [51.2% men, mean age 56.7 ± 14.3 y, median PD duration 31.5 (12.1–57.2) months] were enrolled. Among them, 25.7% were comorbid with diabetes and 28.6% had a history of cardiovascular disease (CVD). After being followed up for up to 43.9 (24.2–50.3) months, 63 had developed cardiovascular events, and 81 patients were died. Among them, the high Pcl group had occurred 39 cardiovascular events and 51 deaths, and the low Pcl group had 24 cardiovascular events and 30 deaths. Kaplan-Meier analysis showed that both the occurrence of cardiovascular events and all-cause mortality were increased in patients with high Pcl. However, after adjusting for important confounders and serum Angiopoietin-2 (Angpt-2) level, Pcl was still an independent risk factor for cardiovascular events [hazard ratio (HR) = 1.006 (1.000–1.012), p = 0.038] but not mortality. On multivariate regression analysis, serum albumin, MTACcr, and body mass index (BMI) were found to be independently associated with Pcl. Conclusion High Pcl is an independent risk factor for cardiovascular events but not all-cause mortality. The prediction of cardiovascular events by Pcl was independent of serum Angpt-2.